Effects of irrigation water salinity on soil salt content distribution, soil physical properties and water use efficiency of maize for seed production in arid Northwest China - Yuan, Chengfu; Feng, Shaoyuan; Wang, Juan; Huo, Zailin; Ji, Quanyi (International Journal of Agricultural and Biological Engineering, 2018)
In order to explore the use of groundwater resources, field experiments were conducted for three consecutive years during 2012-2014 in the Shiyang River basin of Northwest China. Irrigation was conducted using four different water salinity levels that were arranged in a split plot design. These four water salinity levels were s0, s3, s6 and s9 (0.71, 3, 6 and 9 g/L, respectively). The soil salt content, soil bulk density, soil porosity, saturated hydraulic conductivity, plant height, leaf area index and yield of maize for seed production were measured for studying the effects of saline water irrigation on soil salt content distribution, soil physical properties and water use efficiency. It was observed that higher salinity level of irrigation water and long duration of saline water irrigation resulted in more salt accumulation. Compared to initial values, the soil salt accumulation in 0-100 cm soil layer after three years of experiments for s0, s3, s6 and s9 was 0.189 mg/cm3, 0.654 mg/cm3, 0.717 mg/cm3 and 1.135 mg/cm3, respectively. Both greater salt levels in the irrigation water and frequent saline water irrigation led to greater soil bulk density, but poorer soil porosity and less saturated hydraulic conductivity. The saturated hydraulic conductivity decreased with increase in soil bulk density, but increased with improvement in soil porosity. It was noted that the maize height, leaf area index and maize yield gradually decreased with increase in water salinity. The maize yield decreased over 25% and the water use efficiency also gradually declined when irrigated with water containing 6 g/L and 9 g/L salinity levels. However, maize yield following saline water irrigation with 3 g/L decreased less than 20% and the decline in water use efficiency was not significant during the three-year experiment period. The results demonstrate that irrigation with saline water at the level of 6 g/L and 9 g/L in the study area is not suitable, while saline water irrigation with 3 g/L would be acceptable for a short duration together with salt leaching through spring irrigation before sowing. Keywords: saline water irrigation, soil salt content distribution, soil physical properties, maize for seed production, water use efficiency DOI: 10.25165/j.ijabe.20181103.3146 Citation: Yuan C F, Feng S Y, Wang J, Huo Z L, Ji Q Y. Effects of irrigation water salinity on soil salt content distribution, soil physical properties and water use efficiency of maize for seed production in arid Northwest China. Int J Agric & Biol Eng, 2018; 11(3): 137–145.